The Secret of NIMH - OBrien, Robert C. (New York Scholastic Inc., 1982)
The story of a widowed field mouse, Mrs. Frisby, who must move her family from their house in the garden to keep from being plowed under in the spring. Her son, Timothy, is recovering from pneumonia and too weak to be moved. Mrs. Frisby is told to seek out the mysterious rats who live in a rosebush next to the farmhouse... Originally published in hardcover as "Mrs. Frisby and the Rats of NIMH."
Keywords: Children Literature